The virtual slide in the promotion of cytologic and hystologic quality in oncologic screenings - Arrigo Bondi; Paola Pierotti; Paola Crucitti; Stefania Lega (Istituto Superiore di Sanità, 2010)
A regional experience environment in virtual microscopy and digital pathology comprehending the digital cytology is presented. The project has been conducted in Emilia-Romagna and it has been planned for the promotion and the quality assessment in screening cytology and histology for the prevention of the tumors of uterine cervix, breast and colon-rectum cancers. During the project it has been envisaged the design of a dedicated picture archive and communication system (PACS) for cooperative diagnosis, didactics and training, teleconsulting, documentation of rare cases and pilot experiences; furthermore selected cases are catalogued in the PACS with the aim of the check of the diagnostic concordance in the oncologic screening.